Forecasting of delatence behaviour of shallow foundations applying the method of boundary elements - Morhun, A. S. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Stressed-strained state of delatance basement for shallow foundations is considered applying the method of boundary elements.